2015
DOI: 10.1007/s40596-015-0358-1
|View full text |Cite
|
Sign up to set email alerts
|

The Educational Impact of Exposure to Clinical Psychiatry Early in an Undergraduate Medical Curriculum

Abstract: Early exposure to clinical psychiatry through LOCS gives students positive experiences, which improve understanding and awareness of psychiatry. They do not, however, affect stated career intentions for psychiatry as a profession.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 19 publications
3
4
0
Order By: Relevance
“…Our findings, including recommending an 8 week placement of exposure to psychiatry at medical school has been supported by a recent Canadian study [ 22 ], which found that the duration of pre-clerkship exposure to psychiatry predicted the number of students selecting psychiatry as their first choice of discipline [ 22 ]. Respondents in our study also suggested that psychiatry should be introduced earlier in the medical school curriculum to mitigate against negative attitudes developing; this is supported by Brown et al who concluded that earlier exposure promotes awareness and understanding of psychiatry amongst medical students [ 23 ]. Linking with the suggestion given by several of our participants the Royal College of Psychiatrists has expressed the aim to develop UK-wide medical student psychotherapy schemes by 2017 [ 24 , 25 ] and to introduce Balint groups for all medical students, starting ideally at the time of their first contact with patients.…”
Section: Discussionsupporting
confidence: 68%
“…Our findings, including recommending an 8 week placement of exposure to psychiatry at medical school has been supported by a recent Canadian study [ 22 ], which found that the duration of pre-clerkship exposure to psychiatry predicted the number of students selecting psychiatry as their first choice of discipline [ 22 ]. Respondents in our study also suggested that psychiatry should be introduced earlier in the medical school curriculum to mitigate against negative attitudes developing; this is supported by Brown et al who concluded that earlier exposure promotes awareness and understanding of psychiatry amongst medical students [ 23 ]. Linking with the suggestion given by several of our participants the Royal College of Psychiatrists has expressed the aim to develop UK-wide medical student psychotherapy schemes by 2017 [ 24 , 25 ] and to introduce Balint groups for all medical students, starting ideally at the time of their first contact with patients.…”
Section: Discussionsupporting
confidence: 68%
“…Also, students now considered it to be as important as any other field of medicine, and some were even considering it as an option for postgraduation. A similar finding was reported in a qualitative study by Brown et al 26 Likewise, positive changes in attitudes toward psychiatry as a subject were also reported by Tharyan et al, who explored the impact of their clinical teaching program in psychiatry on student knowledge, attitudes, and clinical skills in psychiatry. 11 Many students perceived that the posting helped dispel misconceptions of fear and the “horrible” experience of having to “deal” with patients with psychiatric illness.…”
Section: Discussionsupporting
confidence: 84%
“…These findings are in line with those of a previous study that reported positive changes to students' preconceived notions of psychiatric patients as a result of clinical exposure. 26 Students reported an increase in their knowledge of psychiatric illness-etiology, classification, and management-similar to findings in an earlier study. 15 Students also perceived that the posting helped them hone their skills as doctors in training, enhancing their self-confidence and professional growth.…”
Section: Perceived Impact Of the Postingsupporting
confidence: 82%
“…Some participants thought this caused medical graduates to lose touch with basic sciences. Experiencing the clinical environment in the early years and adding basic courses into the internship period were appreciated by some experts 45,46 …”
Section: Discussionmentioning
confidence: 99%